The genetic diversity and population structure of wild and cultivated Avena species in Ethiopia using a SSR markers - Ashenafi Alemu Tiruneh; Kassahun Tesfaye Geletu; Nasser k Yao; Kifle Dagne Weldegiorgis (Heliyon)
Oats are grains that can be consumed by both animals and humans. They have thrived in Ethiopia, where certain oat species are considered native to the region. This work represents the first investigation of the population structure and genetic diversity of Ethiopian and other country oats. This led the scientists to explore the genetic diversity and population structure of wild and cultivated Ethiopian oats (Avena) species as well as oat cultivated in USA, the Netherlands and Austria. This study's main objective looks to be to investigate the variation in genetic makeup of cultivated and wild oat species. Studying the population structure of the oat species in the germplasm of Ethiopia, USA, the Netherlands and Austria. We used nineteen fluorescent SSR (simple sequence repeat) markers since previous research had indicated that these markers had high PIC (polymorphism information content) values. Five species of Avena were studied among the 176 oat accessions: A. sativa (cultivated oats) and four wild oats, such as A. abyssinica, A. vaviloviana, A. fatua, and A. sterilis. The AMOVA investigation revealed significant genetic distinctions among populations, individuals, and within individuals, explaining 18 % of the variance within populations, 4 % among populations, and 78 % within individuals. The AMOVA analysis of Avena species demonstrated extensive variance, with 33 % variation among species and 67 % within each species, underscoring robust species differentiation. The study also discovered gene interchange between wild oat and cultivated populations, defining two Avena species: domesticated oats and wild oats. Using the STRUCTURE software at K = 2, PCoA, and UPGMA, a distinct genetic structure was displayed in the dataset. Despite variations in ploidy levels and genomes, A. sterilis and A. vaviloviana were determined to be more closely linked, whereas A. abyssinica and A. fatua demonstrated a close association. This research delivers valuable insights for scientists and can be employed in oat breeding programs to improve future oat yield and productivity.